Innovation in Waste Management Policies from the Point of View of Good Governance in West Nusa Tenggara - Indrianti, Iis; Anata, Mario; Zainuddin, Abdul (Prodi Administrasi Publik FISIP UNPAS, 2025)
Effective waste management innovation is key to development and good governance, requiring international collaboration. This qualitative study uses a literary review to analyze existing research, finding Indonesia's rubbish management unsatisfactory due to widespread waste and ineffective policies. Innovation is crucial, and under the lens of Sound Governance, Indonesia needs to partner with leading countries and organizations like UNEP. Technological solutions, such as local incinerators with supportive policies and public awareness, are potential innovations. Ultimately, improving waste management demands innovation, global cooperation, and societal involvement.